Methods and materials for additive manufacturing: A critical review on advancements and challenges - Bhuvanesh Kumar, M; Sathiya, P (Thin-walled structures, 2021)
Additive Manufacturing (AM) is the significantly progressing field in terms of methods, materials, and performance of fabricated parts. Periodical evaluation on the understanding of AM processes and its evolution is needed since the field is growing rapidly. To address this requirement, this paper presents a detailed review of the Additive Manufacturing (AM) methods, materials used, and challenges associated with them. A critical review of the state of art materials in the categories such as metals and alloys, polymers, ceramics, and biomaterials are presented along with their applications, benefits, and the problems associated with the formation of microstructures, mechanical properties, and controlling process parameters. The perspectives and the status of different materials on the fabrication of thin-walled structures using AM techniques have also been discussed. Additionally, the main challenges with AM techniques such as inaccuracy, surface quality, reinforcement distribution, and other common problems identified from the literature are presented. On the whole, this paper provides a comprehensive outlook on AM techniques, challenges, and future research directions. •A review on the basic and recent practices in additive manufacturing techniques is presented.•Use of metallic materials, ceramics, polymers, biomaterials and composites in additive manufacturing are reviewed.•Additive manufacturing in the fabrication of thin-walled structures and scaffolds are discussed.•The challenges in additive manufacturing found in literature and the scopes for future research works also detailed.